THE USE OF COGNITIVE LINGUISTICS APPROACH IN ELT: IMPLEMENTING IMAGE SCHEMA THEORY TO TEACH PHRASAL VERBS IN TOEFL PREPARATION CLASS - Miftah Royani; Dwi Puji Lestari (UAD TEFL International Conference)
Dealing with phrasal verbs (PV) in TOEFL test is one of challengingpartsfor students. They usually learn PV by heart. Nevertheless, their PV mastery has not improved because implementing “blind” memorizing without knowing the concept is harder and will only stay temporarily. Besides, it cannot solve the unfamiliar PV in TOEFL test. Based on the problems, it needs a particular method to make students do not only understand PV meaning easier but also learn it meaningfully. This research is classroom action research. It aims to investigate the students’ improvement in PV mastery using cognitive linguistics approach. The research objects are beginner level of adult learners in TOEFL Preparation class. The data were collected from observation, interview and written test. Cognitive linguistics approach employed in this research was image schema introduced by Johnson and Lakoff (1987).In image schema concept, PV which has abstract meaning is construed in a concrete visualization of CONTAINER to understand the meaning more easily, practical and fun. By implementing cognitive linguistics approach in teaching PV, teachers activate students’ cognition of PV concept which is basically embodied as it arises from human’s mind and body experience. The result shows that there is significant improvement in students’ PV mastery.